USE OF CONCEPT MAP TO IMPROVE SOCIAL STUDIES LEARNING OUTCOMES IN CLASS IV NATURAL RESOURCES MATERIAL AT SD NEGERI 1 KALIGAYAM - SRI INDRAWATI (Universitas Sebelas Maret, 2022)
The aim of the research is to improve student learning outcomes and to determine the effectiveness of the concept map method in Social Sciences subjects, especially in class IV student learning. The research subjects were all 15 grade IV students at SD Negeri 1 Kaligayam, consisting of 13 male students and 2 female students. The research was carried out using the classroom action research method which consisted of 2 cycles. The research results show an increase in student learning outcomes in natural resources material using concept maps. This can be shown by the increase in student learning completeness from the initial conditions, cycle 1 and cycle 2, which was 26.67%; 60%; 93.33%. Increase in the average score in Social Sciences subjects from 68.6; 72.6; 80. The conclusion of the research is that the use of concept map designs in social studies learning on Natural Resources material can improve student learning outcomes.